The Evaluation of the Effects of Two Probiotic Strains on the Oral Ecosystem: A Randomized Clinical Trial - Catherine M. C. Volgenant; Suzette V. van der Waal; Bernd W. Brandt; Mark J. Buijs; Monique H. van der Veen; N. A. M. Rosema; Bernd L. Fiebich; Thorsten Rose; Tim Schmitter; Max Gajfulin; Max Gajfulin; Wim Crielaard; et al. (Frontiers Media S.A., 2022)
IntroductionIn the current study, we evaluated the effectiveness of two well-defined probiotic strains, Lactobacillus paracasei LPc-G110 (CCTCC M 2013691) and Lactobacillus plantarum GOS42 (DSM 32131), during an experimental gingivitis challenge. The primary objective was to evaluate clinically the effectiveness of lozenges containing one of the two oral probiotic strains, compared with placebo lozenges, on the gingival bleeding (bleeding on marginal probing; BOMP change) after a two-week experimental gingivitis period. The secondary objectives were to assess the effects of the test products on gingival health (Modified Gingival Index; MGI), dental plaque accumulation and fluorescence, and the dynamics of immunological and microbiological aspects after the wash-in phase, followed by a two-week period refraining from oral hygiene and a two-week wash-out phase.MethodsThis single-center challenge intervention study was a triple-blind randomized placebo-controlled clinical trial with three parallel groups. The full study population consisted of 117 healthy 18-55 years old human volunteers. Subjects were instructed to use one lozenge, 3 times daily after each meal, containing either L. plantarum, L. paracasei, or lozenges without probiotics (placebo group). After a 2-week wash-in period, the subjects were requested to refrain from any form of oral hygiene for 2 weeks.ResultsThere were no differences in the primary outcome (BOMP change) among the groups. However, gingival health (MGI) in individuals from the groups exposed to the test products recovered better from experimental gingivitis than the individuals in the placebo group (p = 0.021, one-way ANOVA). The two test products inhibited pro-inflammatory cytokine IL-1ß production, measured in saliva, during the experimental gingivitis period. Both test strains significantly reduced bacterial DNA in tongue samples and L. paracasei strain showed stronger microbiome-modulating potential than the L. plantarum strain.ConclusionsThe two tested lozenges with the L. paracasei or L. plantarum strains did show potential for beneficial effects for the oral health of the host during experimental gingivitis to the oral ecosystem.